2014
DOI: 10.1186/1471-2350-15-35
|View full text |Cite
|
Sign up to set email alerts
|

De novo SCN2A splice site mutation in a boy with Autism spectrum disorder

Abstract: BackgroundSCN2A is a gene that codes for the alpha subunit of voltage-gated, type II sodium channels, and is highly expressed in the brain. Sodium channel disruptions, such as mutations in SCN2A, may play an important role in psychiatric disorders. Recently, de novo SCN2A mutations in autism spectrum disorder (ASD) have been identified. The current study characterizes a de novo splice site mutation in SCN2A that alters mRNA and protein products.Case presentationWe describe results from clinical and genetic cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 34 publications
2
41
0
Order By: Relevance
“…Dougherty and colleagues have shown that this circuit is enriched for autism candidate genes (AutDb) but not necessarily genes implicated early in development by de novo LGD events (Xu et al, 2014). Indeed, an examination of the 22 striatal genes implicated in this study with other recently published exomes/genomes (n=3,505) (De Rubeis et al, 2014; Hashimoto et al, 2016; Iossifov et al, 2014; Jiang et al, 2013; Krumm et al, 2015; Lee et al, 2014; Moreno-Ramos et al, 2015; Tavassoli et al, 2014) showed that only one of the genes ( CACNA2D3 ) with evidence for a de novo LGD mutation in an autism proband. Our findings provide further support for this striatal circuit and suggest that multiple de novo regulatory mutations may be an important risk factor for identification of such autism risk genes.…”
Section: Discussionmentioning
confidence: 61%
“…Dougherty and colleagues have shown that this circuit is enriched for autism candidate genes (AutDb) but not necessarily genes implicated early in development by de novo LGD events (Xu et al, 2014). Indeed, an examination of the 22 striatal genes implicated in this study with other recently published exomes/genomes (n=3,505) (De Rubeis et al, 2014; Hashimoto et al, 2016; Iossifov et al, 2014; Jiang et al, 2013; Krumm et al, 2015; Lee et al, 2014; Moreno-Ramos et al, 2015; Tavassoli et al, 2014) showed that only one of the genes ( CACNA2D3 ) with evidence for a de novo LGD mutation in an autism proband. Our findings provide further support for this striatal circuit and suggest that multiple de novo regulatory mutations may be an important risk factor for identification of such autism risk genes.…”
Section: Discussionmentioning
confidence: 61%
“…[21][22][23] The expanded phenotypic spectrum of SCN2A mutations parallels that seen with KCNQ2 and SCN1A and may be broader than currently appreciated. [34][35][36] As yet, no clear genotype-phenotype correlation explains the phenotypic heterogeneity.…”
Section: -Ax T-ap E-hv/t/ht I Gi-c Sf T2-wm T1-bg T-s T-ests Usmentioning
confidence: 96%
“…phenotypes exist: the self-limited autosomal dominant syndrome of BFNIS (with excellent outcome and seizure resolution) and moderate to severe intellectual disability without epilepsy 2,3,[21][22][23]32,33 ; autism may be present. [21][22][23] The expanded phenotypic spectrum of SCN2A mutations parallels that seen with KCNQ2 and SCN1A and may be broader than currently appreciated.…”
Section: -Ax T-ap E-hv/t/ht I Gi-c Sf T2-wm T1-bg T-s T-ests Usmentioning
confidence: 99%
“…(2014) using whole‐exome sequencing found a de novo splice site variation in SCN2A gene in one patient with ASD. This variation (c.476+1G>A) that occurs at exon 4 of SCNA2A gene generates a truncated protein (Tavassoli et al., 2014; Table 2). In addition, the α subunit 8 gene of a Na + channel was associated with ASD and identified by whole‐genome sequencing in a family with ASD.…”
Section: Reviewmentioning
confidence: 99%